Association between fat-soluble vitamin co-exposure patterns and blood pressure in people with hypertension: a cross-sectional study - Dai, Suming; Wang, Ping; Wang, Sijia; Chen, Hong; Cui, Zhixin; Lu, Wenhai; Zhou, Ziyi; Zhang, Nan; Wang, Zhuo; Lin, Tengfei; Song, Yun; Liu, Lishun; et al. (Frontiers in Nutrition, 2025)
BackgroundExisting epidemiological studies investigated the association between a single vitamin and hypertension. However, the potential relationship between the level of circulating multivitamins and blood pressure has not been explored. We aimed to investigate the association between multiple fat-soluble vitamin levels and blood pressure.MethodsA total of 2052 participants with essential hypertension were sampled nationwide. The plasma concentrations of fat-soluble vitamins (A, E, D, and K) were assessed using liquid chromatography coupled with the mass spectrometry method. Participants were categorized into different co-exposure patterns using the unsupervised K-means clustering method. The multiple linear regression model was used for subsequent analyses.ResultsParticipants were classified into two co-exposure patterns of fat-soluble vitamins. The levels of vitamins were relatively low in pattern 1, compared to pattern 2. Participants in pattern 2 had no significantly different blood pressure levels compared to pattern 1. However, the plasma 25-hydroxyvitamin D3 (VD3) levels were negatively associated with SBP (logarithmic 10 transformed) (β = −0.002, 95% CI: −0.004, 0); participants in the fourth α-tocopherol quartile had mean SBP levels that were 1.02% (95% CI: 0.43, 1.61%) greater than those in the lowest quartile (p for trend <0.01). In addition, no significant relationships were found between plasma VA/VK concentrations and blood pressure.DiscussionAlthough no significant association between fat-soluble vitamin co-exposure patterns and blood pressure was found, further analyses could imply that plasma α-tocopherol levels may offset the potential protective effect of plasma VD3 on blood pressure among hypertensive adults. This provided a novel perspective for exploring the joint effects of fat-soluble vitamins on blood pressure. Further studies are warranted to better understand the implications.